Learning Strategies at SMP Muhammadiyah 2 Taman during the Covid 19 Pandemic - Syilviana Eka Purwanto; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the learning strategies during the pandemic at SMP Muhammadiyah 2 Taman, namely learning from home or distance learning. This research uses descriptive qualitative method. The results of this study indicate that the implementation of online learning during the Covid19 pandemic has various problems experienced by teachers, students, and parents. The problems of teachers are in the form of weak mastery of IT and limited access to supervision of students, from students in the form of inactivity in participating in online learning, limited supporting facilities and internet network access, while parents have limited time to accompany their children during online learning.